HUSBAND'S SUPPORT RELATIONSHIP WITH THE INCIDENCE OF POSTPARTUM BLUES IN PUSKESMAS TG.BALAI KARIMUN - Brain Gantoro; Haivan Kusuma Aji (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2020)
Background : The causes of the postpartum blues include predisposing factors which include hormonal factors, physical fatigue, age, parity, pregnancy status, education level and marital status, enabling factors which include socio-economic as well as driving factors which include social support (Mansur in Hasanah, 2014). This study aims to determine the relationship between husband's support and the incidence of postpartum blues. Method : This study used an analytical survey research method with a cross sectional approach. The population in this study were all postpartum mothers who gave birth at the Tanjung Balai Health Center, totaling 113 people. Samples were taken using purposive sampling technique. Data analysis using computer aids through the SPSS program. Result : The results of the chi square statistical test showed that the p value = 0.01, which means that the p value is less than 0.05 (0.01 <0.05). Congclusions : The conclusion is that Ho is rejected and Ha is accepted, this shows that there is a relationship between husband's support for the incidence of postpartum blues.